Listening and Academic Learning: A Survey of Listening Skills among Undergraduates in Lead City University, Ibadan, Nigeria (2018)
Studies have shown that institutions of higher learning in Nigeria pay more attention to reading and writing than listening which has led to undergraduates' experiencing low academic learning. It is against this backdrop that this the study examined the influence of listening skill in student's academic performance. Employing the survey technique and Focus Group Discussions to gather data from a private institution, Lead City University, Ibadan, Nigeria evidence shows students adopting informative listening type for academic study, 76.6% of the respondents affirmed that they adopted the listening skills to understand the general idea of the subject than they do to knowing the detail information which however is not sufficient for thorough academic performance while Pearson Con-elation between listening and academic performance was significant(r=.71,/?<.05) which shows the importance of listening to students' academic performance. There is need for students to combine analytical and critical listening with informative listening to enhance their academic performance.